Digital Signal Processing a Practical Guide for Engineers and Scientists - Smith, Steven (Newnes, 2013)
In addition to its thorough coverage of DSP design and programming techniques, Smith also covers the operation and usage of DSP chips. He uses Analog Devices' popular DSP chip family as design examples. Covers all major DSP topics Full of insider information and shortcuts Basic techniques and algorithms explained without complex numbers.
Keywords: Engineering; Ingénierie; engineering